3x-(2x+5)=69

Simple and best practice solution for 3x-(2x+5)=69 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(2x+5)=69 equation:


Simplifying
3x + -1(2x + 5) = 69

Reorder the terms:
3x + -1(5 + 2x) = 69
3x + (5 * -1 + 2x * -1) = 69
3x + (-5 + -2x) = 69

Reorder the terms:
-5 + 3x + -2x = 69

Combine like terms: 3x + -2x = 1x
-5 + 1x = 69

Solving
-5 + 1x = 69

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 1x = 69 + 5

Combine like terms: -5 + 5 = 0
0 + 1x = 69 + 5
1x = 69 + 5

Combine like terms: 69 + 5 = 74
1x = 74

Divide each side by '1'.
x = 74

Simplifying
x = 74

See similar equations:

| 4y+7-3+y= | | x^3+6x^2+12x+6=0 | | -15+x=47 | | r^2+4=5r | | 3a+1=3.6(9-1) | | 7-5x=-6x+2 | | -6x+4=13+3x | | 2w-3x+5x-w= | | 2x+0.2=-9.8 | | 7-5x=-6+2 | | 2(-4)+-2= | | 0.14(y-5)+0.16y=0.10y-2.1 | | 2(-4)=-2 | | 60-x^2=x^2+9x+30 | | y^(2/3)-216=0 | | 6(y+-2)=4y+-18 | | 0.04(6t-9)=0.24(t+4)-1.32 | | 2t*9t= | | X-2-8=-7 | | B+34=-4+7(b+8) | | 6(4-2)=4y-18 | | -8+b=8 | | 3(5x+2)+4=25 | | 3+2j/j= | | B+34=-4 | | 13/2-3j= | | (9x+6)/x | | 3(3c-1)-1=7c+4 | | 8.1+3.8h-5.6h=-9 | | 3(4k+3)=18 | | 13/2+3j= | | 9x+6/x |

Equations solver categories